Analyzing Consumer Feedback on the Quality of Bus Services in Sidoarjo: A Comprehensive Study: Menganalisis Respon Konsumen terhadap Kualitas Layanan Bus di Sidoarjo: Studi Komprehensif - Selvia Aprilia Ningsih; Nur Maghfirah Aesthetika (Academia Open, 2024)
This research investigates the challenges faced by bus transportation services in Sidoarjo, highlighting the decline in passenger interest over time. Focusing on the year 2015 as a pivotal period for Sidoarjo's bus transportation development, the study employs a qualitative descriptive method to assess service quality through the lenses of reliability, responsiveness, and assurance. Findings reveal that while service officer responsiveness is commendable, improvements are needed in time clarity for reliability, and passenger assurances hinge significantly on the courtesy and friendliness of trans bus service officers. The study aims to provide recommendations for enhancing the appeal of Sidoarjo trans bus services to prevent declining enthusiasm among passengers, emphasizing the importance of comfort factors such as reliability, responsiveness, and assurance. Highlights : Enhancing Service Appeal: Investigating the factors influencing declining passenger interest in Sidoarjo's bus transportation. Reliability and Time Clarity: Identifying the need for improved time clarity to enhance the reliability of the Sidoarjo trans bus system. Assuring Passenger Comfort: Emphasizing the significance of service officer courtesy and friendliness for passenger assurance in bus transportation services Keywords: Bus Transportation, Passenger Satisfaction, Service Quality, Reliability, Responsiveness